Presentation, Management and Outcome of Dengue Fever A Study of 200 Cases - Raman, Md. Habibur; Alam, Abu Yousuf Md. Shahidul; Rahman, AKM Mijanur; Khan, Md. Sarwar; Shapla, Nahid Reaz; Aleem, Mohammad Abdul (Journal of Medicine, 2013)
Background: Dengue is the most rapidly spreading mosquito-borne viral disease in the world1. The rapidly expanding global footprint of dengue is a public health challenge. The endemicity of dengue is also increasing in Bangladesh. This study highlights our current understanding of dengue, including its clinical manifestations, laboratory tests, management and outcome. Objectives: This study was designed to document the presenting features and outcome of Dengue infection in Border Guard personnel. Materials and Methods: It was a prospective observational study which was carried out among outpatient and indoor cases from February 2011 to November 2012 in Border Guard Hospital, Dhaka which is a 300 bedded hospital. Total 200 cases were enrolled. A detailed history, clinical examinations and relevant investigations were done. Data were collected in a predesigned structured questionnaire and analyzed with the help of SPSS-16.0 and Chisquare (X2) Test. Results: A total of 200 adult seropositive Dengue cases of various grade were studied. Among these 152(76%) were male and 48 (24%) were female. Male to female ratio was 3.17:1.The age range of the patients was 18 to 60 years and the mean age 39±12.56 years. Among 200 patients, 112(66%) were Dengue Fever (DF) and 88(44%) were Dengue Haemorrhagic Fever (DHF) including 3(1.5%) cases of DHF Grade lII but none (0%) had Grade-IV DHF. All the patients presented with fever 200(100%), general weakness 200(100%) followed by various skin rash 196(98%), headache 192(96%), myalgia/arthralgia 191(95.5%), retroorbital pain 84(42%). Bleeding manifestation showed in 94(47%) cases of which petechiae was most frequent 86(43%), Haematocrit was normal only in 13(6.5%) patients and 82(41%) had a rise of >20%; Leucopenia was found in 187(93.5%) patients.Only 2(1%) patients had normal platelet count and 03(1.5%) patients had platelet count of less than 10X109 /L. Raised serum alanine aminotransferase (ALT) was observed in 184(92%) of cases. All (200%) the patients recovered completely from the disease; however, one patient subsequently developed Guillein Barre Syndrome. Conclusion: High persistent fever, profound general weakness, myalgia, headache and itchy skin rash were the usual presenting features. Most of the patients recovered well with efficient symptomatic and supportive treatment. Very few cases required blood/platelet transfusion. There was no case fatality in this study group DOI: http://dx.doi.org/10.3329/jom.v14i1.14531 J MEDICINE 2013; 14 : 18-22